Low frequency depression of H-reflexes in humans with acute and chronic spinal-cord injury - Schindler-Ivens, Sheila (2000)
We measured low-frequency depression of soleus H-reflexes in individuals with acute (n=5) and chronic (n=7) spinal-cord injury and in able-bodied controls (n=7). In one acute subject, we monitored longitudinal changes in low-frequency depression of H-reflexes over 44 weeks and examined the relationship between H-reflex depression and soleus-muscle fatigue properties. Soleus H-reflexes were elicited at 0.1, 0.2, 1, 5, and 10 Hz. The mean peak-to-peak amplitude of ten reflexes at each frequency was calculated, and values obtained at each frequency were normalized to 0.1 Hz. H-reflex amplitude decreased with increasing stimulation frequency in all three groups, but H-reflex suppression was significantly larger in the able-bodied and acute groups than in the chronic group. The acute subject who was monitored longitudinally displayed reduced low-frequency depression with increasing time post injury. At 44 weeks post injury, the acute subject’s H-reflex depression was similar to that of chronic subjects, and his soleus fatigue index (assessed with a modified Burke fatigue protocol) dropped substantially, consistent with transformation to faster muscle. There was a significant inverse correlation over the 44 weeks between the fatigue index and the mean normalized H-reflex amplitude at 1, 5, and 10 Hz. We conclude that: (1) the chronically paralyzed soleus muscle displays impaired low-frequency depression of H-reflexes, (2) attenuation of rate-sensitive depression in humans with spinal-cord injury occurs gradually, and (3) changes in H-reflex excitability are generally correlated with adaptation of the neuromuscular system. Possible mechanisms underlying changes in low-frequency depression and their association with neuromuscular adaptation are discussed.